Complex Network Minority Game Model for the Financial Market Modeling and Simulation - Lingyun Chen (Complexity)
This paper proposes a new financial market model based on the analysis of the minority game model. The agent in this model forms a network through information sharing, and the agent uses the minority game model to realize the evolution of the system. To better describe the financial market, we also adopt a prior connection strategy for the model. The network formed by the agent has the characteristics of a scale-free network, and as the initial network connection probability increases, the growth rate of the corresponding agent’s average connection degree increases and then decreases after reaching the peak.